The Positive Outlook Study: A Randomised Controlled Trial Evaluating Online Self-Management for HIV Positive Gay Men - Millard, T.; Agius, P.; McDonald, K.; Slavin, S.; Girdler, Sonya; Elliott, J. (2016)
The aim of this paper was to evaluate the effectiveness of an online self-management program in improving health outcomes and well-being for gay men living with HIV in Australia. The online Positive Outlook Program was based on self-efficacy theory and used a self-management approach to enhance HIV-positive gay men’s skills, confidence and abilities to manage the psychosocial issues associated with HIV in daily life. The 7-week program was delivered in closed groups and comprised information modules, action-planning activities, moderated discussion boards, and weekly peer-facilitated ‘live chats’. A randomised controlled trial was conducted to establish the effectiveness of the Positive Outlook program compared to a ‘usual care’ control. Participants were HIV-positive gay men 18 years or older living in Australia. Primary outcomes were evaluated at three time-points (baseline, post-intervention and 12-week’s post-intervention follow-up) and included HIV-related quality of life (PROQOL-HIV), outcomes of health education (HeiQ) and HIV specific self-efficacy (Positive Outlook Self-Efficacy Scale). A total of 132 gay men with HIV in Australia were randomly allocated to the intervention (n = 68) or usual care control (n = 64) groups. Maximum likelihood marginal-linear modelling indicated significant improvement in the intervention group on the PROQOL-HIV subscales of body change (p = 0.036), social relationships (p = 0.035) and emotional distress (p = 0.031); the HeiQ subscales of health-directed activity (p = 0.048); constructive attitudes and approaches (p = 0.015); skill and technique acquisition (p = 0.046) and health service navigation (p = 0.008); and the Positive Outlook Self-Efficacy Scale on the subscales of relationships (p = 0.019); social participation (p = 0.006); and emotions (p = 0.041). Online delivery of self-management programs is feasible and has the potential to improve quality of life, self-management skills and domain specific self-efficacy for gay men with HIV.